2014
DOI: 10.1177/0890334414531453
|View full text |Cite
|
Sign up to set email alerts
|

The Baby-Friendly Initiative in Spain

Abstract: The Baby-Friendly Initiative (BFI-Spain) was founded in 1995 by members of key professional associations (pediatricians, midwives, obstetricians, and nurses) and some mother-to-mother support groups. The United Nations International Children's Fund was instrumental in supporting the establishment of BFI-Spain as a not-for-profit organization. In 2007, the need for change was identified. A detailed analysis of BFI-Spain identified its main strengths, weaknesses, opportunities, and threats. A new strategic plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In our study, no significant differences were found between the groups studied in step 1 of the Neo-BFHI (written breastfeeding policy); this step is not mandatory until stage 2D of the BFHI in Spain. 25,26 For step 2 of the Neo-BFHI (train all staff to implement this policy), staff training had been implemented more extensively in group 1 than in group 2. Staff training carried out for accreditation of the maternity ward likely has a positive influence on the health care staff in the NICU; this training is 1 of the most effective measures for promoting breastfeeding in NICUs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, no significant differences were found between the groups studied in step 1 of the Neo-BFHI (written breastfeeding policy); this step is not mandatory until stage 2D of the BFHI in Spain. 25,26 For step 2 of the Neo-BFHI (train all staff to implement this policy), staff training had been implemented more extensively in group 1 than in group 2. Staff training carried out for accreditation of the maternity ward likely has a positive influence on the health care staff in the NICU; this training is 1 of the most effective measures for promoting breastfeeding in NICUs.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2011, BFHI accreditation of the maternity wards in Spain, as with other countries, 23,24 has been carried out in 4 stages (Figure 1), with a phased implementation of the Ten Steps. 25,26 In 2015, the requirements for each stage were modified. 25 Participating NICUs were informed that the survey was related to breastfeeding support measures in Spanish NICUs; however, they were not initially told that the analysis of the results would be performed based on the BFHI accreditation process.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, mothers are discharged from hospital earlier than before; thus, efforts to promote breastfeeding need to focus more on the community level (UNICEF UK Baby Friendly Initiative 1999; Lawrence 2011;Haiek 2012;Macaluso et al 2013;Hernandez-Aguilar et al 2014). While the PROBIT study and most systematic reviews have looked at the combined effect of breastfeeding interventions in hospitals and primary care (Spiby et al 2009;Beake et al 2012;Renfrew et al 2012;Haroon et al 2013;Skouteris et al 2014;Sinha et al 2015), a systematic review by the US Preventive Service Task Force focused on interventions in primary care (Chung et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Their suggestions, however, prompted widespread activity. Canada, 4 Gambia, 3 Italy, 5 New Zealand, 6 and Spain, 7 among others, have created Baby-Friendly Community Initiatives, with organizational energy from many sources using a wide range of models, some integrating Baby-Friendly principles into businesses, health care, and pharmacies across entire regions 5 and others creating initiatives that focus primarily, for example, on community health centers. 7…”
mentioning
confidence: 99%